Making Jak sugar the traditional way in Pak Phanang district, Nakhon Si Thammarat province, Thailand: A Case Study - Ngerthaworn, Sutira Chairaksa; Bamrung, Sudrudee (Journal of International Studies, Prince of Songkla University, 2021)
This paper presents fieldwork research into the traditional community method of making Jak sugar (Nipa palm sugar) and other traditional products made from Jak trees (Nypa fruticans, also known as Nipa palm trees). The study was conducted in a community at Pak Phanang district, Nakhon Si Thammarat province, in the south of Thailand. The study employed a qualitative approach using in-depth interviews and observation. We found that the process of making Jak sugar is quite complicated. Firstly, the tools are prepared. Secondly, the Jak tree is selected. Thirdly, its stalks are cut, and the nectar is obtained from the Jak tree. Finally, the Jak sugar is refined from the nectar. Each step uses traditional wisdom that has been passed from generation to generation. In addition, community members make other products from various parts of Jak trees. For example, Jak leaves are used to make hats, a roofing material for houses, cigarette papers, children’s toys, water scoops, and pastry wraps. The Jak leaf sheaths are used for fuel, and Jak stalks are used to make brooms and baskets. The Jak fruits are used to make desserts. These products of the Jak tree are all strongly reflected in, and related to, the way of life of the community.